(3JMQjQ GdbhGYO GdefWbjI, aj TQM GdTeSjIs - (3GdQGRj GdJMJGfj, CHh YHO Gddg, bWH GdOjf, eMeO (B((3Ch eMehO(B) (3Hf eMeO, J (B677 (3g`s ((3Ph GdabGQs)
(3ChdgG (B:s
(3Ef CHgi OQQ JfXe HfjGf GdHjGf (B...(3abO WGd EdMGM GdeTJZdjf Ydi GdeJQOOjf Edi HCf CTQM dge GdQSGdI GdTeSjI hCHjf ajg GdbhGYO GdefWjbI YdeG efge HCfge SCdh YQjfG eGgQG GSJeWQhG (B...s
(3BNQgG (B:s
... (3jbGd GdfGQ GSWajWS ahb GdGSWajSGJ hcGSJYeGd GdCdaGX GdeLGRj aEf GdZGdH eHGOQI GdeYGfj GdMbjbI Edi Gdage cGSJYeGd GdCdaGX GdeLGRjI eTJQcI aEf GdGTJQGc eMd Hage GdeYfi GdeaUhO fYe dh cGf ddSGeY Yde HGdCdaGX JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\38s
(3cTa GdXfhf (B2\1063s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs